CALCULATING THE NUMBER OF GAS PILOTS AND LNG CIRCULATING IN THE MABOG LINE (MARINE BOIL OF GAS) COOLING SYSTEM AT PT. PERTA ARUN GAS - Birri, Chairul; Sariadi, S; Elwina, E (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTAlong with the development of PT. Perta Arun Gas, the challenges to refinery operations also have a significant impact, the company is expected to be able to minimize even the slightest losses that may occur during the industrial process. One of them is that in the flow of the LNG distribution (loading) process to ships, the formation of Boil-Off Gas (BOG) as a result of the expansion in the loading room is inevitable. So that the BOG that forms must be eliminated so as not to cause overpressure in the ship's tank, the B-6803/4 marine flare facility is available to burn the formed BOG so as not to pollute the environment if the gas is directly discharged into the atmosphere. The main tool in this recovery system is the Atomizer, which aims to reduce the temperature of the BOG by atomizing a certain amount of LNG with pressurized vapor gas into the BOG input flow so that heat transfer occurs so that it is in accordance with the specifications of the compressor feed temperature. After a series of calculations, it was found that the total LNG and gas buffer needed to be able to cool the MaBOG line during the loading process with an estimated time of 12.3 hours was 305.6 m3 for LNG and as much as 0.069 mmscfd for gas buffer. This need is in the background with the adjustment of the outlet temperature setting of the second section atomizer (V 6805/13-24) is -140 °C and with the input temperature in HV-68108 which is -80 °C. In addition, after obtaining a calculation model to obtain the value of LNG and gas buffer requirements, the author also tried to conduct some systematic analyses on the influence of LNG and gas buffer requirements on changes in BOG inlet temperature using MS. Excel.keyword : LNG, Boil-Off Gas, Buffer Gas